1993
DOI: 10.1901/jaba.1993.26-121
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Children With Autism to Initiate to Peers: Effects of a Script‐fading Procedure

Abstract: A script that was systematically faded from end to beginning was used to teach peer initiations about recently completed, current, and future activities. The effectiveness of the script-fading procedure was assessed via a multiple baseline design across 4 children with autism. During baseline, the children seldom initiated to peers, although all had previously acquired some functional expressive language and sometimes spontaneously addressed adults. When the script was introduced, peer initiations increased, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
173
0
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(191 citation statements)
references
References 13 publications
12
173
0
6
Order By: Relevance
“…Subsequent scripts corresponding to the other stimuli were introduced after five sessions of 50% correct responding on the current script. When each participant read his script for two sessions, a five-step script-fading procedure was introduced (Krantz & McClannahan, 1993). In…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent scripts corresponding to the other stimuli were introduced after five sessions of 50% correct responding on the current script. When each participant read his script for two sessions, a five-step script-fading procedure was introduced (Krantz & McClannahan, 1993). In…”
Section: Methodsmentioning
confidence: 99%
“…Krantz and McClannahan (1993) reported that after participants were taught to follow a scripted interaction, the script was systematically faded. Throughout the fading process, unscripted interactions or statements increased.…”
Section: Script Fadingmentioning
confidence: 99%
“…There is a significant body of research concerning what was named as incidental teaching and variations and the discussion about their effectiveness in producing generalization. The reader may refer to the literature about the theme for details on naturalistic procedures (Allen & Cowan, 2008;Dunlap & Koegel, 1980;Eikeseth, Smith, Jahr, & Eldevik, 2002;Halle, Baer, & Spradlin, 1981;Halle, Marshall, & Spradlin, 1979;Harris & Handleman, 2000;Hart & Risley, 1968;Koegel, Bimbela & Schreibman, 1996;Koegel, Dyer, & Bell, 1987;Koegel & Egel, 1979;Koegel et al, 2012;Koegel & Koegel, 1990;Koegel, Koegel, Green-Hopkins, & Barnes, 2010;Koegel, O'Dell & Dunlap, 1988;Koegel, O'Dell & Koegel, 1987;Koegel, Werner, Vismara, & Koegel, 2005;Koegel & Williams, 1980;Krantz & McClannahan, 1993, 1998Ledbetter-Cho et al, 2015;Lovaas, 1987;Lovaas, 2003;McGee, Krantz & McClannahan, 1985;Miranda-Linne & Melin, 1992;Mobayeb et al, 2000;Pierce & Schreibman, 1995, 1997Rogers-Warren & Warren, 1980;Schreibman, Kaneko & Koegel, 1991;Sheinkopf & Siegel, 1998;Valenti, Cerbo, Masedu, De Caris, & Sorge, 2010;Warren, McQuarter, & Rogers-Warren, 1984;Williams, Koegel, & Egel, 1981).…”
Section: De Matos P G S De Matos Psychologymentioning
confidence: 99%